2015
DOI: 10.1182/blood-2015-05-646398
|View full text |Cite
|
Sign up to set email alerts
|

MLL leukemia induction by genome editing of human CD34+ hematopoietic cells

Abstract: Key Points Genome editing of primary human HSPCs generates MLL leukemias that model clinical disease features and molecular pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 62 publications
1
50
0
1
Order By: Relevance
“…TALENs were rapidly adopted by the field for genome modifications, and within 5 years of deciphering the recognition code of TALEs, they had overtaken ZFNs future science group To CRISPR & beyond: the evolution of genome editing in stem cells Perspective in popularity (based on number annual of publications, Figure 2). TALENs were used to engineer mouse and human stem cells for targeted developmental studies and disease modeling [52,[55][56][57][58][59][60], on one-cell mouse embryos to generate genomic deletions for knockout studies [61], and for reprogramming of mESCs into iPS cells [62]. TALENs-mediated gene correction has been demonstrated in fibroblasts derived from epidermolysis bullosa patients [63].…”
Section: Zinc Finger Nucleasesmentioning
confidence: 99%
“…TALENs were rapidly adopted by the field for genome modifications, and within 5 years of deciphering the recognition code of TALEs, they had overtaken ZFNs future science group To CRISPR & beyond: the evolution of genome editing in stem cells Perspective in popularity (based on number annual of publications, Figure 2). TALENs were used to engineer mouse and human stem cells for targeted developmental studies and disease modeling [52,[55][56][57][58][59][60], on one-cell mouse embryos to generate genomic deletions for knockout studies [61], and for reprogramming of mESCs into iPS cells [62]. TALENs-mediated gene correction has been demonstrated in fibroblasts derived from epidermolysis bullosa patients [63].…”
Section: Zinc Finger Nucleasesmentioning
confidence: 99%
“…1 HSPCs were isolated from fresh human umbilical cord blood (huCB) obtained from the maternity ward of Stanford Hospital (under an institutional review board-approved research protocol) and maintained as previously described, 9 with the following changes: granulocyte colony-stimulating factor (G-CSF) (50 ng/mL, PeproTech) and UM729 (0.75 mM, STEMCELL Technologies) were added into the culture media. A total of 300 000 CD34 1 cells were nucleofected in one reaction, and the viability (30% to 50%) and nucleofection efficiency (40% to 70% GFP positive) were measured by flow cytometry 2 days after nucleofection.…”
Section: Cd34mentioning
confidence: 99%
“…[3][4][5][6][7][8] Recently, we used custom nucleases for genome editing to activate MLL oncogenes in primary human hematopoietic stem and progenitor cells (HSPCs) that generated leukemia after transplantation in mice. 9 Although this knock-in approach recapitulated many features of the clinical disease presented in patients, it did not reconstitute all genetic aspects of the disease context (eg, lacking the reciprocal product of the translocation). 9 However, induction of reciprocal MLL-AF4 and MLL-AF9 translocations in vitro resulted in translocated cell frequencies that were extremely low, and the cells died out during long-term culture and failed to induce leukemia in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…JAKV617F is an acquired mutation that occurs within the human population, producing a constitutively active Jak2 that drives the formation of myeloproliferative neoplasms (MPNs). [5][6][7][8][9] The JAKV617F mouse model used in this study, which expresses JAKV617F under the regulatory control of the endogenous Jak2 locus, results in the onset of erythrocytosis and thrombocytosis within a number of weeks 10 and can be effectively transferred via bone marrow transplantation. 10 Mascarenhas et al found that if HSCs from the E11.5 AGM region were used as donor material, the expected pathology did not develop (no evidence of erythrocytosis or thrombocytosis was detected over a prolonged period of time and across 2 rounds of transplantation) and the DNA damage that characterizes adult JAKV617F cells was also absent.…”
mentioning
confidence: 99%